2019
DOI: 10.1371/journal.pone.0224881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromuscular electrical stimulation training on muscle size in collegiate track and field athletes

Abstract: The purpose of this study was to examine the effects of neuromuscular electrical stimulation training for 12 weeks on the abdominal muscle size in trained athletes. Male collegiate track and field athletes participated in the present study and were randomly allocated to either training or control groups. Eleven participants of the training group completed a 60-session training program over a 12-week period (23 min/session, 5 days/week) involving neuromuscular electrical stimulation (mostly 20 Hz) for the abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Willand et al 27,37 have shown in rats that electrically stimulating denervated gastrocnemius muscle for 1 hour per day for 1 month yielded significantly bigger muscle mass with stronger twitch forces and more type I fibers. Electrical muscle stimulation has also been studied in humans, from aiding the frail elderly in improving lower limb strength or improving lean body mass in athletes, with diverging results as to its efficacy 38,39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willand et al 27,37 have shown in rats that electrically stimulating denervated gastrocnemius muscle for 1 hour per day for 1 month yielded significantly bigger muscle mass with stronger twitch forces and more type I fibers. Electrical muscle stimulation has also been studied in humans, from aiding the frail elderly in improving lower limb strength or improving lean body mass in athletes, with diverging results as to its efficacy 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…Electrical muscle stimulation has also been studied in humans, from aiding the frail elderly in improving lower limb strength or improving lean body mass in athletes, with diverging results as to its efficacy. 38,39…”
Section: Alternative Methods For Accelerating Motor Recovery After Pe...mentioning
confidence: 99%
“…Functional training is an innovative training method and section, it can improve the disadvantages of traditional mass training. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of identifying such abnormalities of RAM contractility is overcome by its accessibility during C-sections allowing detailed studies of the muscle contractility [15][16][17]. For this analysis, the ex-vivo myography of RAM samples may clarify the knowledge of the pathophysiology of diseases and disorders that affect the RAM [17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…The challenge of identifying such abnormalities of RAM contractility is overcome by its accessibility during C-sections allowing detailed studies of the muscle contractility [15][16][17]. For this analysis, the ex-vivo myography of RAM samples may clarify the knowledge of the pathophysiology of diseases and disorders that affect the RAM [17][18][19][20][21][22]. Although it is widely known that the ex-vivo myography is used to record muscle contractility through the myogram, a tracing graphic recording [18,19,23], that requires tendon attachments through the myograph [24][25][26].…”
mentioning
confidence: 99%